2020
DOI: 10.1371/journal.pone.0239837
|View full text |Cite
|
Sign up to set email alerts
|

Stepping-forward affordance perception test cut-offs: Red-flags to identify community-dwelling older adults at high risk of falling and of recurrent falling

Abstract: The stepping-forward affordance perception test (SF-APT) fills an important gap within the screening of falls risk factors by considering the perception of affordances. The test showed to be a valid instrument for community-dwelling older adults falls risk assessment. The present study aimed to distinguish and test the key outcomes of the SF-APT usable for falls risk assessment in community-dwelling older adults to determine the respective cutoffs. This cross-sectional study enrolled 347 participants (73.1 ± 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
1
4
0
1
Order By: Relevance
“…With respect to the perceived action boundary, the performance-related and exposure risk factor, the present study results con rmed previous ndings [17], showing that the stepping-forward action perceived overestimation is a serious risk for falling.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…With respect to the perceived action boundary, the performance-related and exposure risk factor, the present study results con rmed previous ndings [17], showing that the stepping-forward action perceived overestimation is a serious risk for falling.…”
Section: Discussionsupporting
confidence: 90%
“…Literature usually points the main risk factors for falling as advancing age, female gender, history of previous falls, chronic health conditions (e.g., cardiovascular diseases, disorders of the nervous system, poor vision, or foot impairment), cognitive de cits, poor body composition, low lower limb strength, impaired balance and gait, impaired dual-task performance, environmental hazards and lifestyle habits such as physical (in)activity [7,[12][13][14][15][16]. In addition, a recent study found that the bias of overestimation of the perceived maximum performance for the stepping-forward task is also an important risk factor for falling [17].…”
Section: Introductionmentioning
confidence: 99%
“…Our results indicate that FoF is associated with a higher risk of falling in communitydwelling frail and pre-frail older people. A score of 20 points or more on the FES-I scale is indicative of a three-fold risk of falling in this population, signaling the need for specific prevention strategies [49].…”
Section: Discussionmentioning
confidence: 99%
“…O SF-APT é um instrumento válido para avaliação de risco de quedas de idosos residentes na comunidade. (Pereira et al, 2020).…”
Section: Stepping-forward Affordance Perception Test (Sf-apt)unclassified